Bone-like coatings deposition by using of modern pulsed ion-plasma technology - Zykova, A.V.; Dudin, S.V.; Polozhiy, K.I. (Вопросы атомной науки и техники, 2003)
The technology of synthesis of multilayer coatings on the basis of alumina oxide and structures, like tricalcium phosphate and hydroxylapatite, was suggested by Reactive Ion-Beam Synthesis (RIBS) method in a same vacuum cycle. The substance of the method consists in a physical sputtering of target of compound composition on the specimens with its simultaneous bombardment by intensive ion beams of chemically active gases. The concurrent using of pulsed ion-plasma technology offer the ability to beneficially modify a wide array of surface properties at low temperature; to increase adhesion, density, deposition rate and quality of oxide coatings, to deposit complex multilayer dielectric coatings with ultra disperse structure. The analysis of results obtained in the work, allows to make a conclusion about the advantages of combining of pulsed ion-plasma technology with RIBS method using for the purpose of strong attachment of metal prosthesis in bone tissue and the activation of osseogenesis and osseointegration processes. Технологія нанесення багатошарових покриттів на основі оксиду алюмінію та структур, типу трикальційфосфат та гідроксилапатит запропонована методом реактивного іонно-плазмового синтезу (РІПС) в єдиному вакуумному циклі. Сутність методу полягає у фізичному розпиленні мішені складного стехіометричного складу на підкладенку з її одночасним бомбардуванням інтенсивними іонними пучками хімічно активних газів. Сумісне використання імпульсної іонно-плазмової технології дозволяє успішно змінювати в широкому діапазоні поверхневі властивості отриманих покриттів: підвищити адгезію, щільність, швидкість нанесення та якість оксидних покриттів, а також отримати багатошарові діелектричні покриття з ультрадисперсною структурою. Аналіз отриманих результатів дозволяє зробити висновок відносно значних переваг сумісного використання імпульсної іонно-плазмової технології та методу РІПС з метою забезпечення надійної фіксації металевого протезу у кістковій тканині та активації процесів остеосинтезу та остеоінтеграції. Технология нанесения многослойных покрытий на основе оксида алюминия и структур, типа трикальцийфосфат и гидроксилапатит предлагается методом реактивного ионно-пучкового синтеза (РИПС) в едином вакуумном цикле. Сущность метода состоит в физическом распылении мишени сложного стехиометрического состава на образец с его одновременной бомбардировкой интенсивными ионными пучками химически активных газов. Совместное применение импульсной ионно-плазменной технологии позволяет успешно варьировать в широком диапазоне поверхностные свойства получаемых покрытий: повышать адгезию, плотность, скорость нанесения и качество оксидных покрытий, а также наносить многослойные диэлектрические покрытия с ультрадисперсной структурой. Анализ результатов, полученных в работе, позволяет сделать вывод о преимуществах комбинированного использования импульсной ионно-плазменной технологии и метода РИПС для обеспечения надежной фиксации металлического протеза в костной ткани и активации процессов остеосинтеза и остеоинтеграции.